2012
DOI: 10.1016/j.socscimed.2012.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Does an immigrant health paradox exist among Asian Americans? Associations of nativity and occupational class with self-rated health and mental disorders

Abstract: A robust socioeconomic gradient in health is well-documented, with higher socioeconomic status (SES) associated with better health across the SES spectrum. However, recent studies of U.S. racial/ethnic minorities and immigrants show complex SES-health patterns (e.g., flat gradients), with individuals of low SES having similar or better health than their richer, U.S.-born and more acculturated counterparts, a so-called “epidemiological paradox” or “immigrant health paradox”. To examine whether this exists among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
87
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(100 citation statements)
references
References 62 publications
11
87
2
Order By: Relevance
“…This result supports a recent caution against ignoring or oversimplifying the heterogeneity of the Asian immigrant population because factors that influence physical and mental health are complex and inconsistent across ethnic and cultural subgroups (de Castro et al, 2010;John, de Castro, Martin, Duran, & Takeuchi, 2012). Moreover, our study found that as compared with first-generation immigrants, U.S.-born Asian Americans fared significantly worse on the objective measures of physical and mental health (number of CHCs and any DSM-IV disorder), even though U.S.-born Asian Americans estimated their outcomes to be significantly better on their subjective self-report measures of physical and mental health.…”
Section: Structural Factorssupporting
confidence: 78%
“…This result supports a recent caution against ignoring or oversimplifying the heterogeneity of the Asian immigrant population because factors that influence physical and mental health are complex and inconsistent across ethnic and cultural subgroups (de Castro et al, 2010;John, de Castro, Martin, Duran, & Takeuchi, 2012). Moreover, our study found that as compared with first-generation immigrants, U.S.-born Asian Americans fared significantly worse on the objective measures of physical and mental health (number of CHCs and any DSM-IV disorder), even though U.S.-born Asian Americans estimated their outcomes to be significantly better on their subjective self-report measures of physical and mental health.…”
Section: Structural Factorssupporting
confidence: 78%
“…More recent work specifies more nuanced patterns across and within racial and ethnic minorities attributable to nativity, socioeconomic status, and other protective effects and risk factors [24][25][26][27][28][29]; therefore, all groups do not react the same way to the same stimuli. For our study, we elected to examine the groups, based on their ethnicity or race (Black and Asian as races, Hispanic and Afro-Caribbean as ethnicities) and place of birth (foreign-born as compared to American-born), including other measures known to influence depression, specifically lifetime major depressive disorder.…”
Section: Introductionmentioning
confidence: 99%
“…However, the evidence is mixed and inconclusive. For instance, some studies find migrants exhibit poorer health compared to natives (John, et al, 2012) whilst others show that immigrants tend to have better health and mortality profiles than the native born, especially from the same racial/ethnic group (Markides & Rote, 2015). However, most of these studies relate to a small number of countries or a single country, whilst Ljunge (2016), using the same dataset as the one we employ in this study find no evidence of health differences between migrants and natives with the exception of Muslims.…”
Section: Migrants and Endogeneitymentioning
confidence: 99%